Dinitrogen fixation associated with shoots of aquatic carnivorous plants: is it ecologically important - Sirová, Dagmara; Santrůček, Jiří; Adamec, Lubomír; Bárta, Jiří; Borovec, Jakub; Pech, Jiří; Owens, Sarah M; Santrůčková, Hana; Schäufele, Rudi; Storchová, Helena; Vrba, Jaroslav (Annals of botany, 2014)
BACKGROUND AND AIMS: Rootless carnivorous plants of the genus Utricularia are important components of many standing waters worldwide, as well as suitable model organisms for studying plant-microbe interactions. In this study, an investigation was made of the importance of microbial dinitrogen (N2) fixation in the N acquisition of four aquatic Utricularia species and another aquatic carnivorous plant, Aldrovanda vesiculosa. METHODS: 16S rRNA amplicon sequencing was used to assess the presence of micro-organisms with known ability to fix N2. Next-generation sequencing provided information on the expression of N2 fixation-associated genes. N2 fixation rates were measured following (15)N2-labelling and were used to calculate the plant assimilation rate of microbially fixed N2. KEY RESULTS: Utricularia traps were confirmed as primary sites of N2 fixation, with up to 16 % of the plant-associated microbial community consisting of bacteria capable of fixing N2. Of these, rhizobia were the most abundant group. Nitrogen fixation rates increased with increasing shoot age, but never exceeded 1·3 μmol N g(-1) d. mass d(-1). Plant assimilation rates of fixed N2 were detectable and significant, but this fraction formed less than 1 % of daily plant N gain. Although trap fluid provides conditions favourable for microbial N2 fixation, levels of nif gene transcription comprised <0·01 % of the total prokaryotic transcripts. CONCLUSIONS: It is hypothesized that the reason for limited N2 fixation in aquatic Utricularia, despite the large potential capacity, is the high concentration of NH4-N (2·0-4·3 mg L(-1)) in the trap fluid. Resulting from fast turnover of organic detritus, it probably inhibits N2 fixation in most of the microorganisms present. Nitrogen fixation is not expected to contribute significantly to N nutrition of aquatic carnivorous plants under their typical growth conditions; however, on an annual basis the plant-microbe system can supply nitrogen in the order of hundreds of mg m(-2) into the nutrient-limited littoral zone, where it may thus represent an important N source.
Keywords: Plant Shoots; sekvenční analýza RNA; bakteriální RNA; sekvence nukleotidů; Nitrogen Isotopes; Ecosystem; Nitrogen; RNA, Ribosomal, 16S; izotopy dusíku; výhonky rostlin; voda; amoniové sloučeniny; Bacteria; molekulární sekvence - údaje; Ammonium Compounds; Ecology; Nitrogen Fixation; ekologie; dusík; fixace dusíku; Magnoliopsida; ekosystém; RNA ribozomální 16S; Molecular Sequence Data; Base Sequence; Sequence Analysis, RNA; RNA, Bacterial; Water; Droseraceae